High Spectrum of PTEN Gene Mutations in Iraqi Breast Cancer Patients - Wafaa Sabri Mahood (Journal of Global Pharma Technology, 2018)
Breast cancer conceder the higher tumor rate among Iraqi women. New potential and prognostic markers are required to identify those women. PTEN gene (phosphatase and tensin homolog deleted from chromosome 10) is tumor suppressor; its mutations in breast cancer are well reported in many populations but not in the Iraqi people. The main purpose of this research was to identify the PTEN mutation spectrum as predictive marker in Iraqi patients with breast cancer and benign lesion. The mutations in the 7th exon of PTEN gene was analyzed on thirty tow Iraqi females with breast disease, twenty women were diagnosed breast cancer and six women with precursor lesions of the breast (benign) in addition to six healthy women served as reference (controls). Results showed several mutations including thirty different mutations in malignant samples, the most five were characterized by high alteration rates75% (15/20), at position 115833 and 115950 these are T>G and T>A followed by 65%(13/20) and 50 % (10 /20) at positions 115921 and 115843 respectively this is G>C, other more mutations frequency 45% (9/ 22) at position 115912 this is G>T .We also detected an insertion G and T between (115833-115834) in 20%(4/20) and 10 % (2/20) respectively .Comparison of mutations between malignant and benign patients showed the frequency of several mutations in three sits (115833, 115843 and 115912) were appear in both benign and malignant patients may indicating to important role of the three sits in initiation and progression of breast cancer. Other two positions (115832, 115949) also have high mutations rate were found only in malignant patients indicating that these positions may have a role in progression of breast cancer. In conclusion we believe that PTEN gene is a promising biomarker that could be useful in detection of breast cancer patients and predicting the prognostic state of those women.Keywords: Iraq, PETN gene, Breast cancer.